2019
DOI: 10.1038/s41598-019-44529-0
|View full text |Cite
|
Sign up to set email alerts
|

Visual modelling supports the potential for prey detection by means of diurnal active photolocation in a small cryptobenthic fish

Abstract: Active sensing has been well documented in animals that use echolocation and electrolocation. Active photolocation, or active sensing using light, has received much less attention, and only in bioluminescent nocturnal species. However, evidence has suggested the diurnal triplefin Tripterygion delaisi uses controlled iris radiance, termed ocular sparks, for prey detection. While this form of diurnal active photolocation was behaviourally described, a study exploring the physical process w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…We, therefore, used visual modelling and showed that an ocular spark is strong enough to increase the achromatic contrast in a scorpionfish's pupil above a triplefins's perception threshold over distances that coincide well with the nearest approaches seen in the third field experiment. As has been made clear before [15], this study once more indicates that diurnal active photolocation is not fail-proof, as shown by the predictions from the visual modelling and by the fact that even clear-hatted triplefins approached scorpionfish within ranges that may fall within the striking range of a scorpionfish [41][42][43]. Diurnal active photolocation is also not strictly required for detecting a scorpionfish, as shown by the response of shaded triplefins to scorpionfish relative to stones.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…We, therefore, used visual modelling and showed that an ocular spark is strong enough to increase the achromatic contrast in a scorpionfish's pupil above a triplefins's perception threshold over distances that coincide well with the nearest approaches seen in the third field experiment. As has been made clear before [15], this study once more indicates that diurnal active photolocation is not fail-proof, as shown by the predictions from the visual modelling and by the fact that even clear-hatted triplefins approached scorpionfish within ranges that may fall within the striking range of a scorpionfish [41][42][43]. Diurnal active photolocation is also not strictly required for detecting a scorpionfish, as shown by the response of shaded triplefins to scorpionfish relative to stones.…”
Section: Discussionsupporting
confidence: 53%
“…We conclude that diurnal active photolocation is a mechanism that supplements a triplefin's ability to detect scorpionfish. The chromatophore patch on the lower iris of the triplefin T. delaisi on which the ocular spark is focused behaves like a diffuse, Lambertian reflector in the equatorial plane of vision [15]. This produces a light field that covers most of the hemispherical zone over a short distance, as seen by a single eye.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations